FSM-Gear weight-based energy-efficient protocol for illegal logging monitoring using firefly synchronization - Mutiara, Giva Andriana (2022)
Wireless Sensor Network (WSN) technology applies most monitoring processes since it is a general platform for many domain applications. Therefore, WSN can be applied to minimize illegal logging. WSN consists of many sensor nodes, and to communicate among sensor nodes; the network should be robust with high-signal strength, high computation, and low- power consumption. However, the challenge comes from the management level of power consumption on minimizing the power consumption. The enhanced and appropriate algorithm should be applied according to the actual environment in the forest. The effort of low-power algorithm was conducted in several stages, such as (1) randomly distributed localization technique; (2) randomly applied clustering and cluster head selection; (3) the use of Time Division Multiple Access (TDMA) synchronization; and (4) how to formulate the distance factor to the power emitted by sensor nodes not based on the real environment. This research proposes a new weight-based, energy-efficient multi-hop protocol: Firefly Synchronization Multi-Hop Geographic Energy-Aware Routing protocol (FSM-GEAR). The research objective is to have a low-power consumption protocol applied in a model network based on the actual environment suitable for illegal logging characteristics. The methodology was applied by using a modified design science framework. The new stages are applied based on the Received Signal Strength Indicator (RSSI) distance of sensor nodes, and residual energy becomes a weight parameter based on the actual environment in this protocol. The Firefly Universal Synchronization Algorithm (FUSA)-based was adapted in the synchronization phase as one of the efforts to reduce the delay that occurs because of the clock-time differences from each sensor node. The optimum network model has resulted in five cluster heads network clustering. This model was used to examine and test the FSM- GEAR Protocol and the previous M-GEAR. The result was then compared. Both protocols were run using MATLAB and examined in network performance parameters, such as (1) the number of alive nodes versus rounds to determine the network lifetime; (2) remaining energy versus round to determine the residual energy and energy consumption; and (3) energy consumption versus the number of transmission packets to determine the throughput. Based on the testing result, the FSM-GEAR protocol minimized the energy consumption by about 12.5% than the M-GEAR protocol. FSM-GEAR protocol proved that it reduced power consumption, maximized throughput, and had a more extended network lifetime than the M- GEAR protocol. The improvement of the proposed protocol has also made many contributions in terms of a better energy-efficient WSN multi-hop protocol for illegal logging. In addition, this research has an opportunity to be implemented in the real environment